Annual Report 2012: Unfolding results: CCAFS research into action - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
In 2012, we have seen policy advances in climate change adaptation and mitigation in more than ten countries where research products from CCAFS have been used to inform decision-making processes. CCAFS also works with major development actors in order to get research results to scale. Key actors like the development banks have used CCAFS analyses to guide investment decisions about climate-change adaptation. A ten year US$50 million programme focused on collecting wild relatives of crops and pre-breeding for climate-change adaptation has used CCAFS results to prioritize investments. Evidence-based decision making in agriculture and natural resource management starts with evidence from the practices of farmers, fishers and pastoralists.